Antioxidative and antiproliferative activities of isolated compounds from Prunus domestica: an in vitro study - Naveen Dhingra; Rajesh Sharma; Anand Kar (International Journal of Phytomedicine, 2013)
In this investigation the antioxidant as well as antiproliferative activities of different isolated compounds from ethyl acetate fraction of Prunus domestica (peel + flesh) were studied in two human breast cancer cell lines, MCF-7 and MDA-MB-468. Free radical scavengering as done with 2, 2-diphenyl-1-picrylhydrazyl (DPPH) study indicated different degrees of antioxidative activity of the isolated compounds such as chlorogenic acid, protocatechuic acid, vanillic acid, ferulic acid, p-coumaric acid and rutin. However maximum antioxidative activity was observed in chlorogenic acid with IC50 of 0.115 mg/ml. With respect to antiproliferative potential, chlorogenic acid also exhibited the maximum antiproliferative activity on MCF-7 and protocatechuic acid on MDA-MB-468 human breast cancer cell lines. This appears to be the first report that provides a comparative account on the antioxidant and antiproliferative property of some isolated active compounds of the Indian variety of fruit, Prunus domestica.